Effect of the CeO2 synthesis method on the behaviour of Pt/CeO2 catalysis for the water-gas shift reaction. (13th August 2019) - Pastor-Pérez, L.; Ramos-Fernández, E.V.; Sepúlveda-Escribano, A.
Abstract: A comparative study of three different ceria synthesis procedures (template- and MW- assisted hydrothermal synthesis and urea homogeneous precipitation) is reported in this paper. The obtained materials were employed as supports for Pt nanoparticles, and the Pt/CeO2 catalysts were evaluated in the WGS reaction under model and realistic conditions. The influence of the support, e.g., its morphology and electronic properties, has been studied in detail by means of XRD, H2 -TPR, XPS, UV–Vis spectroscopy and toluene hydrogenation (for metal dispersion assessment). The catalytic performance of the samples is directly correlated with the modification of the electronic properties, as a result of the preparation method used. The conventional homogeneous precipitation method with urea resulted to be the best option, leading to enhanced ceria reducibility and adequate Pt dispersion, which in turns resulted in a very efficient WGS catalyst. Graphical abstract: Image 1 Highlights: Three different ceria synthesis routes have been compared. The synthesis procedure modulates the redox and electronic properties of CeO2 . Pt dispersion and metal-support interaction are depend on the morphology of CeO2 . The highest activity with realistic conditions was shown by the Pt/CeO2 urea catalyst.